2004
DOI: 10.1007/s00702-003-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume and cell proliferation after acute and chronic clozapine or haloperidol treatment

Abstract: The dentate gyrus contains progenitor cells possessing the capacity to proliferate until and throughout adulthood. There is little information about the influence of antipsychotics on cell proliferation. To address this, we investigated the influence of acute and chronic haloperidol and clozapine treatment on the total number of newly dividing cells and hippocampal volume using an animal model with doses equivalent to the therapeutic range in humans. Rats were treated with either acute or 28 days haloperidol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
1
30
2
4
Order By: Relevance
“…In fact, such progenic effect was previously observed after only long-term (2 to 3 weeks) treatment with various ADs including fluoxetine (Malberg et al, 2000;Santarelli et al, 2003;Malberg and Duman, 2003;Mnie-Filali et al, 2007b). To our knowledge, only non-selective 5-HT 7 receptors antagonists (such as atypical neuroleptics risperidone or clozapine) were used to assess the effects on hippocampal cell proliferation but the results were not conclusive (Halim et al, 2004;Kodama et al, 2004;Schmitt et al, 2004). Also, Sarkisyan and Hedlund (2009) reported that the rate of cell proliferation in the DG was identical in 5-HT 7 receptor wild-type and knock-out mice even if such mice present antidepressant-like phenotypes (Guscott et al, 2005;Hedlund et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, such progenic effect was previously observed after only long-term (2 to 3 weeks) treatment with various ADs including fluoxetine (Malberg et al, 2000;Santarelli et al, 2003;Malberg and Duman, 2003;Mnie-Filali et al, 2007b). To our knowledge, only non-selective 5-HT 7 receptors antagonists (such as atypical neuroleptics risperidone or clozapine) were used to assess the effects on hippocampal cell proliferation but the results were not conclusive (Halim et al, 2004;Kodama et al, 2004;Schmitt et al, 2004). Also, Sarkisyan and Hedlund (2009) reported that the rate of cell proliferation in the DG was identical in 5-HT 7 receptor wild-type and knock-out mice even if such mice present antidepressant-like phenotypes (Guscott et al, 2005;Hedlund et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Animals were treated with daily intramuscular injections of haloperidol dissolved in Dimethyl sulfoxide (DMSO) (Fisher Scientific, Fair Lawn, NJ, USA) (1mg/kg/day, n=11), or vehicle (DMSO) (n=11) for 28 days (Halim et al, 2004, Schmitt et al, 2004, Spurney et al, 1999. Twenty-four hours after the last injection, the animals were sacrificed and brains were immediately removed, dissected, and frozen in isopentane.…”
Section: Acquisition and Processing Of Rodent Brain Tissuementioning
confidence: 99%
“…Antidepressant drugs enhance neurogenesis in the adult rodent dentate gyrus of the hippocampus (Malberg et al, 2000;Duman et al, 2001;Santarelli et al, 2003), and animal models of depression are associated with decreased neurogenesis in the same brain structure (Malberg and Duman, 2003;Santarelli et al, 2003). Several studies have investigated the effects of antipsychotic drug on cell genesis in a number of brain regions; however, these studies have reported inconsistent findings (Dawirs et al, 1998;Wakade et al, 2002;Halim et al, 2004;Schmitt et al, 2004;Wang et al, 2004). This failure to establish a clear link between antipsychotic drug administration and cell genesis is likely attributable to not only administration of different antipsychotic drugs but also to the use of different protocols to detect cell genesis that are sensitive to mixed or different populations of proliferating and maturing cell types.…”
Section: Introductionmentioning
confidence: 98%